2020
DOI: 10.1136/rapm-2020-101435
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the brachial plexus and its implications for daily clinical practice: regional anesthesia is applied anatomy

Abstract: Safety and effectiveness are mandatory requirements for any technique of regional anesthesia and can only be met by clinicians who appropriately understand all relevant anatomical details. Anatomical texts written for anesthetists may oversimplify the facts, presumably in an effort to reconcile extreme complexity with a need to educate as many users as possible. When it comes to techniques as common as upper-extremity blocks, the need for customized anatomical literature is even greater, particularly because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
0
26
1
1
Order By: Relevance
“…In our clinical practice, when these anomalies are observed, we perform ISB 2-3 cm caudal to the variation point, if possible. Vascular structures, which will restrict the spread of LA or inhibit the needle advancement such as dorsal scapular artery, can be present between the cervical roots in this region [8,9]. While an artery crossing the roots or trunks was revealed in 23% of the patients in the study by Gutton et al, the rate was observed as 4.5% in the current study.…”
Section: Original Articlecontrasting
confidence: 41%
See 1 more Smart Citation
“…In our clinical practice, when these anomalies are observed, we perform ISB 2-3 cm caudal to the variation point, if possible. Vascular structures, which will restrict the spread of LA or inhibit the needle advancement such as dorsal scapular artery, can be present between the cervical roots in this region [8,9]. While an artery crossing the roots or trunks was revealed in 23% of the patients in the study by Gutton et al, the rate was observed as 4.5% in the current study.…”
Section: Original Articlecontrasting
confidence: 41%
“…The variations associated with some nerves, muscles and vascular structures in the interscalene area may affect the technique of the procedure [7][8][9]. In the presence of such variations, especially in the cephalad approach and ISB conducted with low volume, the scalene muscles can prevent the spread of local anesthesia (LA) by acting as a barrier [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The brachial plexus is an important peripheral nerve plexus in the human body. It is composed of C5–C8, T1 nerve roots, and innervates the sensory and motor functions of the shoulder and upper limbs [ 9 ]. Once injured, the disability rate is high, which seriously affects the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Interscalene Sub-areas (Figure 5), Feigl [5] notified two anatomically distinct spaces are contained in the interscalene gap:…”
Section: Boundariesmentioning
confidence: 99%
“…The superior and middle trunks may be separated from the inferior trunk at the level of subclav ican ar ter y (Zuckerkandl-Sebileau ligaments) [5].…”
Section: Arrangement Of Divisionsmentioning
confidence: 99%